Resistance and virulence gene analysis and molecular typing of Escherichia coli from duck farms in Zhanjiang, China - Luo, Shuaishuai; Liao, Cuiyi; Peng, Jinju; Tao, Songruo; Zhang, Tengyue; Dai, Yue; Ding, Yuexia; Ma, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The widespread use of antibiotics in animal agriculture has increased the resistance of Escherichia coli, and pathogenic E. coli often harbor complex virulence factors. Antimicrobial resistance in pathogenic bacteria can cause public health problems. Correlation analyses of the resistance, virulence, and serotype data from the pathogenic bacteria found on farms and in the surrounding environment can thus provide extremely valuable data to help improve public health management. Methods In this investigation, we have assessed the drug resistance and virulence genes as well as the molecular typing characteristics of 30 E. coli strains isolated from duck farms in the Zhanjiang area of China. Polymerase chain reaction was used to detect the drug resistance and virulence genes as well as serotypes, and whole-genome sequencing was used to analyze the multilocus sequence typing. Results The detection rates for the oqxA resistance gene and fimC virulence gene were highest (93.3%, respectively). There were no correlations between the drug resistance and virulence gene numbers in the same strain. The epidemic serotype was O81 (5/24), ST3856 was an epidemic sequence type, and strains I-9 and III-6 carried 11 virulence genes. The E. coli strains from the duck farms in the Zhanjiang area were thus found to have a broad drug resistance spectrum, various virulence genes, complex serotypes, and certain pathogenicity and genetic relationship. Discussion Monitoring the spread of pathogenic bacteria and the provision of guidance regarding the use of antibiotics in the livestock and poultry industries will be required in the future in the Zhanjiang area.